2018
DOI: 10.1103/physrevb.98.245119
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced entanglement in a magnonic Floquet topological insulator

Abstract: When irradiated via high frequency circularly polarized light, the stroboscopic dynamics in a Heisenberg spin system on a honeycomb lattice develops a next nearest neighbor (NNN) Dzyaloshinskii-Moriya (DM) type term 37 , making it a magnonic Floquet topological insulator. We investigate the entanglement generation and its evolution on such systems -particularly an irradiated ferromagnetic XXZ spin-1 2 model in a honeycomb lattice as the system parameters are optically tuned. In the high frequency limit, we com… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 59 publications
(64 reference statements)
0
14
0
Order By: Relevance
“…Such form of exchange can also emerge from the truncated dipolar exchange [15,16]. Furthermore, for α = −1, the antisymmetric form reduces to the DMI, which was first proposed by Dzyaloshinsky and Moriya [17,18] and had attracted continued interest [19][20][21][22][23][24][25]. The DMI has been proved to be a key factor in explaining the magnetic properties in LiMnPO 4 [26], Ni 3 V 2 O 8 [27], MnSi [28,29] and CoFeB [30], etc.…”
Section: Model and Phase Diagrammentioning
confidence: 95%
“…Such form of exchange can also emerge from the truncated dipolar exchange [15,16]. Furthermore, for α = −1, the antisymmetric form reduces to the DMI, which was first proposed by Dzyaloshinsky and Moriya [17,18] and had attracted continued interest [19][20][21][22][23][24][25]. The DMI has been proved to be a key factor in explaining the magnetic properties in LiMnPO 4 [26], Ni 3 V 2 O 8 [27], MnSi [28,29] and CoFeB [30], etc.…”
Section: Model and Phase Diagrammentioning
confidence: 95%
“…One of the advantages of the current results is that the photoinduced topological magnons and the chiral edge modes can be tuned by varying the amplitude and polarization of the laser field. Another interesting feature of irradiated Kitaev magnets is that the existence of the Floquet topological magnon insulators does not require the explicit time-reversal symmetry breaking term from the second-order virtual-photon absorption and emission processes, which is mandatory for the existence of Floquet topological states in irradiated graphene [36,37] and irradiated honeycomb ferromagnets [42][43][44]. We also showed that irradiated Kitaev magnets exhibit a tunable photoinduced thermal Hall effect.…”
mentioning
confidence: 86%
“…In the presence of an intense laser light, electron spin degree of freedom in magnetic insulators can couple to laser field through different processes [48][49][50][51][52][53][54][55][56][57][58]. In particular, quantized spin waves (magnons) are the oscillations of the spin magnetic dipole moment of an electron.…”
Section: Theory Of Laser-irradiated Honeycomb Ferromagnet Crimentioning
confidence: 99%
“…/ ω is the photon emission and absorption term. The first term H 0 is the original time-independent spin Hamiltonian with renormalized interactions J ⊥ ij → J ⊥ ij J 0 (α m ) for S x S x and S y S y couplings, J z ij → J ij for S z S z coupling, and D → DJ 0 (α m ), where J n (x) is the Bessel function of order n. For dominant J 1 interaction, the second term yields a photoinduced DM interaction is of the form [51,[56][57][58]…”
Section: A Light Propagation Along the Z-directionmentioning
confidence: 99%
See 1 more Smart Citation